The Impact of Bariatric Surgery on Type 2 Diabetes Mellitus and the Management of Hypoglycemic Events - Kassem, Mahmoud Attia Mohamed; Durda, Michael Andrew; Stoicea, Nicoleta; Cavus, Omer; Sahin, Levent; Rogers, Barbara (Frontiers in Endocrinology, 2017)
Recent studies discussed the benefit of bariatric surgery on obese patients diagnosed with type 2 diabetes mellitus (T2DM). Several factors play an essential role in predicting the impact of bariatric surgery on T2DM, such as ABCD score (age, BMI, C-peptide, and duration of the disease), HbA1c, and fasting blood glucose, incretins [glucagon-like peptide-1 (GLP-1) and gastric inhibitory peptide (GIP)]. DiaRem score known to include factors such as age, HbA1c, medication, and insulin usage used to predict the remission of T2DM, but it has some limitations. An extensive literature search was conducted on PubMed and Google Scholar using keywords such as gastric bypass, T2DM, bariatric surgery, GLP-1, GIP, and post bariatric hypoglycemia. Restrictive-malabsorptive procedures are most effective in treating T2DM patients based on changes induced in appetite through regulation of gastrointestinal hormones, with decreased hunger and increased satiation. We provide a review of bariatric surgery influence on T2DM and management of post-intervention hypoglycemic events. Post-bariatric surgery hypoglycemia is a serious complication especially when patients develop life-threatening neuroglycopenia with loss of consciousness and seizure. The avoidance of this adverse event may be achieved by strict dietary modification including a restriction on carbohydrates as well as foods with high glycemic index. Further research will provide more information on post-bariatric surgery hyperinsulinemic hypoglycemia pathophysiology and management.